2021
DOI: 10.1111/aos.14927
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of diabetic retinopathy (DR) in the UK population of Gloucestershire

Abstract: Purpose: To estimate prevalence and incidence of diabetic retinopathy (DR) in a UK region by severity between 2012 and 2016 and risk factors for progression to proliferative DR (PDR). Methods: Electronic medical records from people with diabetes (PWD) ≥18 years seen at the Gloucestershire Diabetic Eye Screening Programme (GDESP) and the hospital eye clinic were analysed (HEC). Prevalence and incidence of DR per 100 PWD (%) by calendar year, grade and diabetes type were estimated using log-linear regression. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…A total of 7,593 (0.4%) urgent referrals were due to PDR and 52,597 (2.5%) to pre-proliferative diabetic retinopathy or maculopathy [ 43 ]. Overall, prevalence of DR was assessed as being 36.6% and that of PDR was 3.1% in 2016 (analysed in a subpopulation of 35,873 diabetics screened within the Gloucestershire Diabetic Eye Screening Programme) [ 44 ].…”
Section: Dr: Global Statistics and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 7,593 (0.4%) urgent referrals were due to PDR and 52,597 (2.5%) to pre-proliferative diabetic retinopathy or maculopathy [ 43 ]. Overall, prevalence of DR was assessed as being 36.6% and that of PDR was 3.1% in 2016 (analysed in a subpopulation of 35,873 diabetics screened within the Gloucestershire Diabetic Eye Screening Programme) [ 44 ].…”
Section: Dr: Global Statistics and Trendsmentioning
confidence: 99%
“…In addition, early diagnosis and management of DR are generally acknowledged as a key in reducing diabetes-related visual impairment [ 82 ]. For instance, following the implementation of a national screening program designed to identify vision-threatening DR, blindness from DR was significantly reduced in Iceland, England, and Wales [ 43 , 44 ].…”
Section: Targeted Mitigationmentioning
confidence: 99%
“…This is higher than the global prevalence (34.6%) [ 25 ]. We reported a higher prevalence of DR compared to North America, the UK, Italy, China and Germany (33.3%, 36.6% 27.6%, 27.9%and 25.8%, respectively) [ 26 , 27 , 28 , 29 , 30 ]. On the other hand, we reported a lower DR prevalence compared to France and Norway (50.1% and 61%, respectively) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 98%
“…A UK retrospective cohort analysis found that 46% of those with newly diagnosed Type 2 diabetes who were retinopathy‐free developed DR after 7 years 22 . This study used the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) database and ascertained DR status using diagnosis codes, 22 although the validity of the database is unclear, particularly regarding those without DR. Another UK population‐based study reported an 8.5% annual incidence of new DR in 2016 in those with Type 2 diabetes using electronic medical records 6 . In a review of population‐based studies of Type 1 and/or Type 2 diabetes conducted after 2000, the annual incidence of DR ranged from 2.2% to 12.7% 5 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggested a substantial lifetime DR risk but this may no longer apply given temporal trends in other complications. A recent review showed that the incidence of DR in people with Type 2 diabetes was lower in studies conducted after versus before 2000, 5 and a UK study showed a significant decrease in the incidence of DR between 2013 and 2016 6 . Furthermore, the global prevalence of DR appears to have decreased from 34.6% in a pooled analysis of studies conducted between 1980 and 2008 7 to 22.2% in a more recent analysis in which studies up to 2020 were included 8 .…”
Section: Introductionmentioning
confidence: 99%